Quasi-Experimental study of effects of lighting on rest, activity and melatonin in postpartum women - Cristina Furtado Volcov; Eliana Moreira Pinheiro; Miriam Harumi Tsunemi; Fernanda Gaspar do Amaral; Ariane Ferreira Machado Avelar; Jennifer Hocking; Kelly Pereira Coca (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to compare the parameters of the activity/rest cycle of early postpartum breastfeeding women under a controlled and uncontrolled long wavelength ray light regimen. Methods: quasi-experimental study with breastfeeding women and their babies during postnatal rooming-in, São Paulo, Brazil. Participants were allocated to either an experimental (intervention) or a comparison group. The intervention involved exposure of the woman in a controlled room with artificial long wavelength ray light at night. Each woman's level of 6-sulfatoxymelatonin at 24 hours and activity/rest times was analyzed. Results: the mean activity/rest times of women in the experimental and comparison groups were similar. The mean percentages of total load of 6-sulfatoxymelatonin during the day and night were similar (p=0.09). At 24 hours, the experimental group presented a significantly lower mean percentage of total load compared to the comparison group (p=0.04). Conclusions: women who stayed in the room with long-wavelength artificial light showed no difference in activity/rest and 6-sulfatoxymelatonin levels in the early postpartum period.